Validation of the Persian Translation of the Swallowing Disturbance Questionnaire in Parkinson’s Disease Patients - Ali Rajaei; S. Abolfazl Azargoon; Mohammad Hussein Nilforoush; Ebrahim Barzegar Bafrooei; Fereshteh Ashtari; Ahmad Chitsaz (Parkinson's Disease)
Dysphagia, as a common finding in Parkinson’s disease (PD) patients, was estimated to be present in 80–95% of this population during different stages of the disease. The Swallowing Disturbance Questionnaire (SDQ) was created as a self-rated dysphagia screening tool in PD. According to the guidelines for cross-cultural adaptation, Persian version of this questionnaire (SDQ-P) was developed. 59 Persian patients (39 men and 20 women) participated in the study. They responded to the SDQ-P and underwent videofluoroscopic swallowing study (VFSS). Aspiration during VFSS was compared with questionnaire results for each individual. Cronbach’s alpha coefficient for the questionnaire was 0.86 and based on SDQ-P 15 patients (25.4%) were dysphagic, while 10 patients (16.9%) showed aspiration during VFSS. SDQ-P sensitivity and specificity in predicting aspiration were 96.7 and 91.2%; therefore, the SDQ-P could be a prognostic tool for aspiration. The positive predictive value (PPV), the negative predictive value (NPV), and the pre- and posttest probabilities of aspiration were 0.67, 1, 16.9%, and 66.7%, respectively. In summary, this study demonstrated the reliability and also the feasibility of SDQ-P for screening of aspiration in Iranian patients with PD. Further evaluation of SDQ-P in larger subject population would be suggested.